The Factors Influencing Fatigue of Postpartum Mothers - Astuti, Yuni; Indriastuti, Nur Azizah (Universitas Muhammadiyah Yogyakarta, 2021)
Background: Postpartum mothers are likely to experience physical and psychological changes. A new role as a parent provides new tasks for mothers in baby care. Most postpartum mothers experience fatigue after labor. Postpartum fatigue is affected by the baby and family. This study aims to identify factors associated with postpartum fatigue.Method: A cross-sectional study was designed. The sample in this research was 102 postpartum mothers who lived with her family in Bantul Yogyakarta. They were taken by using simple random sampling. The data were collected through the Postpartum Fatigue Scale (PFS), infant characteristic questionnaire (ICQ), and social support questionnaire. Factors associated with postpartum fatigue were analyzed using multiple logistic regressions.Results: Most of the respondents had a moderate level of fatigue (48%). Social support was found significant as the determinant factor of postpartum mother (AOR=4,38, 95% CI 1,709 – 11,256, p= 0,002).Conclusion: Respondents with a low social support level showed a significantly higher level of postpartum fatigue than respondents with good social support. It is essential to assist the family in helping mothers in infant care and postpartum care in the postpartum period. The factor associated with postpartum fatigue included infant temperament and family income.